Innovation Footprint and New Value Chain from Pematang Johar Village - Dian Setyorini; Isra Rafika Sihombing; Sipnarong Kanchanawongpaisan; Muhammad Hafiz Abd.Rashid; Phan Bao Giang; Khoirul Amri; ⁠Teuku Muhammad Syahrizal; Diego Faustine Karim (Eastasouth Institute, 2025)
Pematang Johar Village is one of the agricultural villages with abundant rice production. However, a portion of the harvest results in low-quality rice such as broken grains, dull color, and leftover rice from daily consumption. This problem leads to economic inefficiency and increased food waste. Through this community service program, a new value chain innovation was introduced by processing rice waste into rice crackers. This innovation was chosen because of easily available raw materials, cultural consumption habits, and its potential to reduce food waste while creating local culinary identity. The production process is simple, low-cost, and offers wide marketing opportunities both online and offline. The program results show an increase in community knowledge and skills, establishment of a small business group, and the birth of a new culinary identity for Pematang Johar Village.